Coal-based porous sodium ion battery hard carbon negative electrode material and preparation method thereof
Through the improved preparation method, humic acid and zinc chloride are used for crosslinking and activation, the problem of difficult control of pore size of existing sodium ion battery hard carbon anode materials is solved, and coal-based porous hard carbon anode materials with high energy density and good cycle stability are prepared.
Patent Information
- Application Number
- CN202310515172.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-09
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-05-09
AI Technical Summary
When existing sodium ion battery hard carbon anode materials are produced on a large scale, the pore size is difficult to control, the process is complex and the cost is high, resulting in insufficient energy density and cycle stability of the battery.
By grinding, pre-carbonizing, mixing with humic acid and zinc chloride, heating activation, pickling treatment and heat treatment, coal-based porous hard carbon anode material with uniform pores and increased coal seam spacing is prepared.
The pore uniformity and coal seam spacing of hard carbon negative electrode materials are achieved, which improves the first-time coulomb efficiency and cycle stability of the battery and reduces production costs.
Smart Images

Figure CN116715239B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery negative electrode materials, and in particular to a coal-based porous sodium ion battery hard carbon negative electrode material and a preparation method thereof. Background Art
[0002] With the development of society, people attach great importance to the shortage of energy resources and the environmental problems caused by fossil energy, and the research and development of new energy storage materials is imminent. Lithium-ion batteries have become the preferred renewable energy storage material due to their high energy density, and have therefore developed rapidly. However, due to the limited content of lithium in the earth's crust, it is difficult to meet people's long-term demand for energy. Sodium and lithium are in the same main group, with similar chemical properties and similar energy storage mechanisms. The production and manufacturing of sodium-ion batteries can directly utilize the existing production equipment and design experience of lithium-ion batteries, which is conducive to the rapid production and application of sodium-ion batteries. Sodium is the sixth most abundant element on the earth and is distributed all over the world. It has the characteristics of abundant raw material resources, low price, and high specific capacitance. Because the ionic radius and relative atomic mass of sodium ions are greater than those of lithium ions, it is not conducive to the rapid migration of sodium ions in electrode materials and electrolytes, making the energy density of sodium-ion batteries lower than that of lithium-ion batteries. Therefore, sodium-ion batteries are more suitable for large-scale energy storage fields that do not require particularly high energy density.
[0003] Hard carbon is one of the main application materials for the negative electrode of sodium-ion batteries. The microstructure of hard carbon is amorphous carbon with long-range disorder and short-range order. This structural feature is conducive to ion or electron transport and has good application prospects in lithium-ion or sodium-ion batteries. For hard carbon materials, they are generally modified by changing the morphology and adjusting the pore structure. The pore structure includes porosity and pore size distribution. The pore structure greatly affects the performance of hard carbon materials. Activation is also one of the effective methods to improve the sodium storage performance of hard carbon.
[0004] As a known technology, nano- and porous treatments on hard carbon negative electrode materials can improve the gram capacity performance. However, nano- and porous structures will inevitably introduce certain defects. For example, in Chinese patent CN 114906836 A, anthracite and diethanolamine are mixed at a suitable temperature and pressure, and the molten diethanolamine can effectively penetrate into the micropores of the anthracite. Then the pore-forming agent in the micropores of the raw material anthracite is directly heated and cracked from the solid state to produce a large amount of gas, which increases the size of the micropores. However, the above method has defects. The molten pore-forming agent is difficult to be evenly dispersed in the coal during large-scale production, and the pore size is difficult to control. For example, in Chinese patent CN 112645305 A, pores are made by pre-physical / chemical activation, and then the preset pore structure is used to suppress the long-range development of microcrystals in the anthracite during the high-temperature carbonization process, thereby obtaining a hard carbon material with a short-range ordered graphite-like crystal structure. The above method adds a pre-activation step, prolongs the preparation time, increases the energy consumption of the preparation process, has a complex process, and is costly, which is not conducive to large-scale mass production. Summary of the invention
[0005] In view of the above problems, the purpose of the present invention is to provide a coal-based porous hard carbon negative electrode material for sodium ion batteries and a preparation method thereof. The prepared hard carbon negative electrode material has uniform pores and increased coal layer spacing. As the negative electrode material of the sodium ion battery, the battery has a high first coulombic efficiency and good cycle stability.
[0006] In order to achieve the above object, the present invention provides a method for preparing a coal-based porous sodium ion battery hard carbon negative electrode material, comprising the steps of:
[0007] (1) grinding the coal raw material to obtain coal powder;
[0008] (2) pre-carbonizing the pulverized coal to obtain carbonized pulverized coal;
[0009] (3) mixing the carbonized coal powder with humic acid, then adding zinc chloride, stirring and mixing, to obtain a mixed material;
[0010] (4) heating and activating the mixed material to obtain activated coal powder;
[0011] (5) acid-washing the activated coal powder, then washing with water and drying;
[0012] (6) heat treating the material dried in step (5) to obtain a hard carbon negative electrode material.
[0013] Compared with the prior art, the preparation method of the coal-based porous sodium ion battery hard carbon negative electrode material of the present invention is to add humic acid for cross-linking and zinc chloride for activation, the phosphate group in the humic acid is hydrolyzed and reacts with carbon under high temperature conditions, so that the coal is activated to form pores mainly composed of micropores, and the pore size is uniform, so that uniform pores are obtained; and after the humic acid is heat-treated, the humic acid cross-linking produces steric hindrance, improves the microcrystalline interlayer spacing, and increases the coal interlayer spacing; the inhibitory effect of humic acid cross-linking on graphitization helps to form a short-range ordered and long-range disordered structure, which is more conducive to the storage of sodium ions, and zinc chloride has a catalytic dehydration effect at high temperature, so that the hydrogen and oxygen atoms in the coal are separated in the form of water vapor to form a large number of pores, and then the zinc chloride is removed by acid washing, so as to obtain a hard carbon material with a short-range ordered graphite-like crystal structure with a large interlayer spacing, uniform pores, and developed pores. The coal after heat treatment has a lower specific surface area and good porosity, which can reduce the occurrence of side reactions during the first charge and discharge process, so that the battery has a high first coulomb efficiency and good cycle stability.
[0014] In some embodiments, in step (1), the coal raw material is selected from at least one of anthracite, bituminous coal, sub-bituminous coal, lignite, and peat.
[0015] In some embodiments, in step (1), the particle size of the coal powder after grinding is controlled to be 200 mesh to 400 mesh. As an example, the particle size of the coal powder can be, but is not limited to, 200 mesh, 240 mesh, 280 mesh, 300 mesh, 350 mesh, 380 mesh, and 400 mesh. It can be understood that grinding the coal raw material into fine powder is conducive to subsequent uniform dispersion. The specific grinding method can be to first crush the coal raw material and then use a jet mill for processing, but it is not limited to this.
[0016] In some embodiments, in step (2), the pre-carbonization treatment is performed in an inert atmosphere, and the treatment temperature is 500-800° C., preferably 600° C., and the pre-carbonization is beneficial to the subsequent activation.
[0017] In some embodiments, in step (3), the mass ratio of coal powder to humic acid is 1-10:1. Further, the amount of coal powder used is greater than the amount of humic acid used. The mass ratio of coal powder to humic acid is 2-10:1. Further, the mass ratio of coal powder to humic acid is 2-8:1. As an example, the mass ratio of coal powder to humic acid may be but is not limited to 2:1, 4:1, 5:1, 6:1, 8:1.
[0018] In some embodiments, in step (3), the mass ratio of coal powder to zinc chloride is 1-10:1. Further, the amount of coal powder is greater than the amount of zinc chloride. The mass ratio of coal powder to zinc chloride is 2-10:1. Further, the mass ratio of coal powder to zinc chloride is 2-8:1. As an example, the mass ratio of coal powder to zinc chloride can be but is not limited to 2:1, 4:1, 5:1, 6:1, 8:1.
[0019] In some embodiments, after the coal powder and humic acid are mixed, a suitable dispersant may be added to improve the dispersion effect.
[0020] In some embodiments, in step (4), the temperature of the activation treatment is 400-900°C, preferably 600°C.
[0021] In some embodiments, in step (5), the acid used for pickling treatment is selected from at least one of sulfuric acid, hydrochloric acid, hydrofluoric acid, and nitric acid. As an example, a mixture of hydrochloric acid and hydrofluoric acid is used for pickling treatment.
[0022] In some embodiments, in step (5), the temperature of the pickling treatment is 60-90°C, preferably 80°C.
[0023] In some embodiments, in step (6), the heat treatment is performed at a temperature of 1200-1500° C., preferably 1400° C., in an inert atmosphere.
[0024] Correspondingly, the present invention also provides a coal-based porous sodium-ion battery hard carbon negative electrode material, which is prepared by the above-mentioned preparation method of the coal-based porous sodium-ion battery hard carbon negative electrode material.
[0025] The coal-based porous sodium ion battery hard carbon negative electrode material of the present invention has the following technical effects:
[0026] (1) The preparation method of the present invention uses humic acid crosslinking and zinc chloride activation to pyrolyze some oxygen-containing groups to form gas pores. The pore size is concentrated in micropores and the pores are uniform, which is conducive to large-scale industrial production.
[0027] (2) The preparation method of the present invention uses humic acid cross-linking and zinc chloride activation, which requires low temperature, simple process and energy saving;
[0028] (3) The method of the present invention is simple, low-cost, and environmentally friendly. The obtained coal-based hard carbon material has the characteristics of high compaction density, high first reversible capacity and first coulombic efficiency, and excellent processing performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a SEM image of the hard carbon negative electrode material prepared in Example 1 of the present invention.
[0030] Figure 2 The charge and discharge curves of the hard carbon negative electrode materials prepared in Examples 1-3 and Comparative Example 1 of the present invention are shown. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0032] Example 1
[0033] A method for preparing a coal-based porous sodium ion battery hard carbon negative electrode material comprises the following steps:
[0034] (1) Grinding: The anthracite raw material is crushed and jet milled in sequence to obtain fine coal powder, and the particle size of the coal powder is controlled to be 300 mesh;
[0035] (2) Pre-carbonization: The coal powder is placed in a box furnace and carbonized in an inert atmosphere at 600°C for 3 hours, then cooled to room temperature to remove volatiles to obtain carbonized coal powder;
[0036] (3) Mixing: adding the carbonized coal powder and humic acid in a mass ratio of 5:1 to a deionized water solution, adding a small amount of dispersant sodium dodecylbenzene sulfonate, heating at 70°C, stirring for 30 minutes, and drying, then adding zinc chloride (the mass ratio of coal powder to zinc chloride is 5:1) and mechanically stirring to obtain a mixed material;
[0037] (4) Activation: Activate the mixed material at 600°C for 2 hours to obtain activated coal powder;
[0038] (5) impurity removal and drying: the activated coal powder is pickled with a mixture of hydrochloric acid and hydrofluoric acid, stirred at a constant temperature of 80°C for 10 hours, and then washed with water until neutral to obtain a washed product, which is then dried;
[0039] (6) Heat treatment: The material dried in step (5) is subjected to a high temperature heat treatment at 1400° C. for 3 h in an inert atmosphere, then naturally cooled to room temperature, and passed through a 325-mesh sieve to obtain a finished product, i.e., a hard carbon negative electrode material.
[0040] Example 2
[0041] A method for preparing a coal-based porous sodium ion battery hard carbon negative electrode material comprises the following steps:
[0042] (1) Grinding: crushing and jet milling the bituminous coal raw materials in sequence to obtain fine coal powder, and the particle size of the coal powder is controlled to be 350 mesh;
[0043] (2) Pre-carbonization: The coal powder is placed in a box furnace and carbonized in an inert atmosphere at 600°C for 3 hours, then cooled to room temperature to remove volatiles to obtain carbonized coal powder;
[0044] (3) Mixing: adding the carbonized coal powder and humic acid in a mass ratio of 2:1 to a deionized water solution, adding a small amount of dispersant sodium dodecylbenzene sulfonate, heating at 70°C, stirring for 30 min, and drying, then adding zinc chloride (the mass ratio of coal powder to zinc chloride is 5:1) and mechanically stirring to obtain a mixed material;
[0045] (4) Activation: Activate the mixed material at 600°C for 2 hours to obtain activated coal powder;
[0046] (5) impurity removal and drying: the activated coal powder is pickled with a mixture of hydrochloric acid and hydrofluoric acid, stirred at a constant temperature of 80°C for 10 hours, and then washed with water until neutral to obtain a washed product, which is then dried;
[0047] (6) Heat treatment: The material dried in step (5) is subjected to a high temperature heat treatment at 1400° C. for 3 h in an inert atmosphere, then naturally cooled to room temperature, and passed through a 325-mesh sieve to obtain a finished product, i.e., a hard carbon negative electrode material.
[0048] Example 3
[0049] A method for preparing a coal-based porous sodium ion battery hard carbon negative electrode material comprises the following steps:
[0050] (1) Grinding: The anthracite raw material is crushed and jet milled in sequence to obtain fine coal powder, and the particle size of the coal powder is controlled to be 300 mesh;
[0051] (2) Pre-carbonization: The coal powder is placed in a box furnace and carbonized in an inert atmosphere at 600°C for 3 hours, then cooled to room temperature to remove volatiles to obtain carbonized coal powder;
[0052] (3) Mixing: adding the carbonized coal powder and humic acid in a mass ratio of 8:1 to a deionized water solution, adding a small amount of dispersant sodium dodecylbenzene sulfonate, heating at 70°C, stirring for 30 minutes, and drying, then adding zinc chloride (the mass ratio of coal powder to zinc chloride is 5:1) and mechanically stirring to obtain a mixed material;
[0053] (4) Activation: Activate the mixed material at 600°C for 2 hours to obtain activated coal powder;
[0054] (5) impurity removal and drying: the activated coal powder is pickled with a mixture of hydrochloric acid and hydrofluoric acid, stirred at a constant temperature of 80°C for 10 hours, and then washed with water until neutral to obtain a washed product, which is then dried;
[0055] (6) Heat treatment: The material dried in step (5) is subjected to a high temperature heat treatment at 1400° C. for 3 h in an inert atmosphere, then naturally cooled to room temperature, and passed through a 325-mesh sieve to obtain a finished product, i.e., a hard carbon negative electrode material.
[0056] Comparative Example 1
[0057] A method for preparing a coal-based porous sodium ion battery hard carbon negative electrode material comprises the following steps:
[0058] (1) Grinding: The anthracite raw material is crushed and jet milled in sequence to obtain fine coal powder, and the particle size of the coal powder is controlled to be 300 mesh;
[0059] (2) Pre-carbonization: The coal powder is placed in a box furnace and carbonized in an inert atmosphere at 600°C for 3 hours, then cooled to room temperature to remove volatiles to obtain carbonized coal powder;
[0060] (3) Mixing: mixing the carbonized coal powder and zinc chloride in a mass ratio of 5:1, and mechanically stirring to obtain a mixed material;
[0061] (4) Activation: Activate the mixed material at 600°C for 2 hours to obtain activated coal powder;
[0062] (5) impurity removal and drying: the activated coal powder is pickled with a mixture of hydrochloric acid and hydrofluoric acid, stirred at a constant temperature of 80°C for 10 hours, and then washed with water until neutral to obtain a washed product, which is then dried;
[0063] (6) Heat treatment: The material dried in step (5) is subjected to a high temperature heat treatment at 1400° C. for 3 h in an inert atmosphere, then naturally cooled to room temperature, and passed through a 325-mesh sieve to obtain a finished product, i.e., a hard carbon negative electrode material.
[0064] Figure 1 The SEM image of the hard carbon negative electrode material prepared in Example 1 is shown. Figure 1 It can be seen that the hard carbon negative electrode material has a large number of pores.
[0065] Figure 2 The charge and discharge curves of the hard carbon negative electrode materials prepared in Examples 1-3 and Comparative Example 1 are shown. Figure 2 It can be seen that the first discharge specific capacity in comparative example 1 is 260 mAh / g, and the first discharge specific capacity in embodiments 1-3 is above 290 mAh / g, and even reaches 310 mAh / g, with fast charging and large capacity.
[0066] The hard carbon negative electrode materials prepared in Examples 1 to 3 and Comparative Example 1 were subjected to relevant performance tests, and the results are shown in Table 1.
[0067] Table 1 Test results
[0068]
[0069] It can be seen from the results in Table 1 that, compared with Comparative Example 1, the hard carbon negative electrode materials of Examples 1 to 3 of the present invention have better reversible capacity and high first coulombic efficiency, which can reduce the occurrence of side reactions during the first charge and discharge process, thereby making the battery have high first coulombic efficiency and good cycle stability.
[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a coal-based porous hard carbon negative electrode material for a sodium ion battery, characterized in that: Includes steps: (1) grinding the coal raw material to obtain coal powder; (2) pre-carbonizing the pulverized coal to obtain carbonized pulverized coal; (3) mixing the carbonized coal powder with humic acid, then adding zinc chloride, stirring and mixing to obtain a mixed material, wherein the mass ratio of the coal powder to the humic acid is 1-10:1, and the mass ratio of the coal powder to the zinc chloride is 1-10:1; (4) heating and activating the mixed material to obtain activated coal powder, wherein the activation treatment temperature is 400-900° C.; (5) acid-washing the activated coal powder, then washing with water and drying; (6) heat treating the material dried in step (5) to obtain a hard carbon negative electrode material.
2. The method for preparing a coal-based porous sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step (1), the coal raw material is selected from at least one of anthracite, bituminous coal, sub-bituminous coal, lignite and peat.
3. The method for preparing a coal-based porous sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step (1), the particle size of the pulverized coal is controlled to be 200 to 400 meshes.
4. The method for preparing a coal-based porous sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step (2), the pre-carbonization treatment is carried out in an inert atmosphere at a treatment temperature of 500-800°C.
5. The method for preparing a coal-based porous sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step (5), the acid used for pickling treatment is selected from at least one of sulfuric acid, hydrochloric acid, hydrofluoric acid and nitric acid.
6. The method for preparing a coal-based porous sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step (5), the temperature of the pickling treatment is 60-90°C.
7. The method for preparing a coal-based porous sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step (6), the heat treatment is performed at a temperature of 1200-1500° C. in an inert atmosphere.
8. Coal-based porous sodium ion battery hard carbon negative electrode material, characterized in that: The material is prepared by the method for preparing the coal-based porous sodium ion battery hard carbon negative electrode material according to any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation method of anthracite-based hard carbon material combining pre-activation pore-forming and high-temperature carbonization
CN112645305A
Hard carbon negative electrode material, preparation method and sodium ion battery
CN114906836A
Method for preparing activated carbon material with humic acid as raw material and application of activated carbon material
CN103641117A
Method for preparing nitrogen-enriched porous carbon material for supercapacitor by taking lignite as raw material
CN104817082A